Factors influencing consumers’ willingness to purchase Musang King durian (Durio Zibethinus) in Raub, Pahang, Malaysia - Rosmiza Mohd Zainol; Mohamad Syahrul Nizam Ibrahim; Liew, Song Shen; Fatin Umaira Muhamad Azian; Nazahah Rahim (Malque Publishing, 2025)
Musang King durian (Durio Zibethinus), a variety of Malaysia, is in high demand in the Chinese market and is also popular among local consumers. However, the premium pricing of this variety influenced by supply and demand limits access for many segments of local consumers. The question arises as to whether the local community can afford it by examining the factors driving consumers' willingness to purchase Musang King durian. A descriptive study was conducted with 110 respondents from Raub, Pahang, which is well known as the largest Musang King production area in Malaysia. The study revealed that the main factors driving consumers' willingness to purchase Musang King durian are its unique taste, consumers’ income and consumer purchases. Although the income range of the local population is low to moderate, the distinctive taste and purchasing power of consumers are key drivers for purchasing this premium variety. Moreover, other factors, such as the market price of Musang King, the seasonality of its production, and the influence of promotions through acquaintances and social media, also play a role in influencing consumers' decisions to purchase Musang King durian. The aforementioned factors have increased the demand for Musang King durian both locally and internationally, although its supply is contingent upon production seasons and weather conditions. Therefore, durian growers and the government should collaborate to ensure that supply meets the required levels of production and quality. This is essential to meet the growing demand from both local consumers and international markets. Additionally, attention should be given to expanding the potential market for downstream products derived from Musang King durian so that the market is not focused solely on upstream production.